2023
DOI: 10.3390/tropicalmed8020096
|View full text |Cite
|
Sign up to set email alerts
|

Civil Engineering and Malaria Risk: A Descriptive Study in a Rural Area of Cubal, Angola

Abstract: (1) Background: Angola is among the high-burden countries with malaria cases globally. After 2013, we suspected an increase in the number of malaria cases in Cubal (Angola), previously in decline. Our objective was to evaluate the incidence rate in Cubal, overall and by neighborhood, for 2014, 2015, and 2016. (2) Methods: A retrospective, observational study was performed in Cubal (Angola) from January 2014 to December 2016, including all patients with a microbiologically confirmed diagnosis, treated at Cubal’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A retrospective and observational study carried out at the HNSP between January 2009 and December 2013 showed a prevalence of 14.2% for P. falciparum using thick blood films as unique diagnostic method [ 23 ]. However, more recently, another retrospective study conducted between January 2014 and December 2016 showed an increase in the incidence of malaria in Cubal using both microscopy (27.2%) and RDTs (50.6%) [ 30 ]. Our study was conducted during May and July 2022 showing similar results for microscopy (33.5%) and RDTs (49%).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective and observational study carried out at the HNSP between January 2009 and December 2013 showed a prevalence of 14.2% for P. falciparum using thick blood films as unique diagnostic method [ 23 ]. However, more recently, another retrospective study conducted between January 2014 and December 2016 showed an increase in the incidence of malaria in Cubal using both microscopy (27.2%) and RDTs (50.6%) [ 30 ]. Our study was conducted during May and July 2022 showing similar results for microscopy (33.5%) and RDTs (49%).…”
Section: Discussionmentioning
confidence: 99%